2022
DOI: 10.1136/bmjopen-2022-062461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of completion of maternity continuum of care and its associated factors in Ethiopia: a systematic review and meta-analysis

Abstract: ObjectiveThe present study aimed to estimate the pooled prevalence of completion of the maternity continuum of care (CoC) and its associated factors in Ethiopia.Study designSystematic review and meta-analysis.Study settingEthiopia.Study participantsA total of 6245 reproductive-age women were included.Primary outcomeThe pooled prevalence of completion of the maternity CoC.Secondary outcomeFactors associated with completion of the maternity CoC.MethodsWe systematically searched international databases such as Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…12 It indicates an improvement in the maternal continuum of care and availability of emergency obstetric care in Ethiopia. 33 , 34 In contrast, this implies an increase in primary and lower uterine segment CS. 35 Moreover, it is vital to achieve SDG-3 36 by decreasing maternal morbidity and mortality related to repeated CS.…”
Section: Discussionmentioning
confidence: 99%
“…12 It indicates an improvement in the maternal continuum of care and availability of emergency obstetric care in Ethiopia. 33 , 34 In contrast, this implies an increase in primary and lower uterine segment CS. 35 Moreover, it is vital to achieve SDG-3 36 by decreasing maternal morbidity and mortality related to repeated CS.…”
Section: Discussionmentioning
confidence: 99%
“…According to ndings in Ethiopia, the prevalence of completion of maternity CoC was 25.82% (22). Another similar study reported that the pooled prevalence of maternal healthcare service utilization on a complete continuum was 25.51% (23).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that sociodemographic factors are signi cantly associated with all elements of the continuum of maternal health care (36). The mothers age (19,21), residence (9,15,19,22,27), educational status (9,11,12,15,16,20,21,23,27,29,34), marital status (20,25), socioeconomic status (17, 19-22, 25, 27), employment status (23)(24)(25)(26), and exposure to media (9, 11, 15, 20-22, 25, 28, 34) and mothers' autonomy in decision-making (11,12,15,22,24,27,29) signi cantly contributed to the utilization of a continuum of maternal health care services. The maternal and child health continuum of care was determined by different maternal and child health service-related factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations